FUNDAMENTALS OF MEDICINAL BIOMAGNETISM - Viapiana Bossa, Camila; Viapiana, Cristiane; Gattás Person, Ivan; Maria Oliveira Lima, Márcia; Viapiana Bossa, Adriane (Health and Society, 2023)
Medicinal Biomagnetism (MB) is a therapy for the prevention, diagnosis, and treatment of diseases using static magnetic fields. It is based on physical-chemical and physiopathological principles. To understand the technique, it is necessary to present the concepts of magnetism, potential of hydrogen, magnetic resonance, entropy, symbiosis, homeostasis, and the rheology of fluids. Understanding the fundamentals of MB is the first step towards the construction of a scientific language, as well as for the understanding and clinical interpretation of its results. This study is a narrative review of the literature that aims to present the fundamentals of MB within the principles of physics, chemistry, biology, physiology, and biochemistry to serve as a basis for technique application and for new scientific research projects in the area. Most of the studies that have applied the technique could not be considered for analysis due to a lack of the necessary methodological rigor, while others were derived from end-of-course papers and are not yet published. Regarding the investigated fundamentals, a vast body of literature was found, and its relationship with MB can be explored. It is concluded that there is coherence between the theoretical bases already substantiated in science and the principles of MB.